Peran Pegadaian Syariah Dalam Inklusi Keuangan Masyarakat Indonesia: Studi Literatur Tentang Aksesibilitas Layanan Pembiayaan Berbasis Gadai - leste, fauziyah mutiara; Fuadi, Fatih; Iqbal, Muhammad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines the strategic role of Islamic Pawnshops in expanding financial inclusion for Indonesian society through pawn-based financing services. The research employs a qualitative approach with literature study analyzing various sources including scientific journal articles, research reports, and official financial institution publications from 2021-2025. Thematic content analysis was applied to identify patterns, relationships, and main themes related to Islamic pawn service accessibility. Research findings indicate that Islamic Pawnshops contribute significantly to improving financial service accessibility for underserved segments of society, particularly low-income groups and micro, small, and medium enterprise actors. Implementation of rahn contract principles emphasizing justice and transparency without usury elements becomes the main advantage in attracting people who have preferences for Islamic financial products. Digital transformation through online service platform innovation and Gold Bank products has expanded geographical reach and increased operational efficiency. However, challenges such as low digital literacy and limited technology infrastructure remain obstacles that need to be addressed. This research recommends strengthening Islamic financial education programs, developing transparent marketing strategies, and inter-institutional collaboration to optimize the role of Islamic Pawnshops in realizing an inclusive and equitable financial system in Indonesia.